Red Clover (Trifolium pratense) and Zigzag Clover (T. medium) - A Picture of Genomic Similarities and Differences - Dluhošová, Jana; Ištvánek, Jan; Nedělník, Jan; Řepková, Jana (Frontiers in plant science, 2018)
The genus clover (Trifolium sp.) is one of the most economically important genera in the Fabaceae family. More than 10 species are grown as manure plants or forage legumes. Red clover's (T. pratense) genome size is one of the smallest in the Trifolium genus, while many clovers with potential breeding value have much larger genomes. Zigzag clover (T. medium) is closely related to the sequenced red clover; however, its genome is approximately 7.5x larger. Currently, almost nothing is known about the architecture of this large genome and differences between these two clover species. We sequenced the T. medium genome (2n = 8x = 64) with ∼23× coverage and managed to partially assemble 492.7 Mbp of its genomic sequence. A thorough comparison between red clover and zigzag clover sequencing reads resulted in the successful validation of 7 T. pratense- and 45 T. medium-specific repetitive elements. The newly discovered repeats led to the set-up of the first partial T. medium karyotype. Newly discovered red clover and zigzag clover tandem repeats were summarized. The structure of centromere-specific satellite repeat resembling that of T. repens was inferred in T. pratense. Two repeats, TrM300 and TrM378, showed a specific localization into centromeres of a half of all zigzag clover chromosomes; TrM300 on eight chromosomes and TrM378 on 24 chromosomes. A comparison with the red clover draft sequence was also used to mine more than 105,000 simple sequence repeats (SSRs) and 1,170,000 single nucleotide variants (SNVs). The presented data obtained from the sequencing of zigzag clover represent the first glimpse on the genomic sequence of this species. Centromeric repeats indicated its allopolyploid origin and naturally occurring homogenization of the centromeric repeat motif was somehow prevented. Using various repeats, highly uniform 64 chromosomes were separated into eight types of chromosomes. Zigzag clover genome underwent substantial chromosome rearrangements and cannot be counted as a true octoploid. The resulting data, especially the large number of predicted SSRs and SNVs, may have great potential for further research of the legume family and for rapid advancements in clover breeding.
Keywords: zigzag clover karyotype; centromeric repeats; FISH; sequencing; comparative analysis